Zearalenone causes ovarian damage and abnormal estradiol secretion in meat rabbits by inducing oxidative stress and inflammatory responses - Wu, Fengyang; Wang, Fengxia; Tang, Zhaohong; Yang, Xinyu; Liu, Yanhua; Zhao, Man; Liu, Shudong; Han, Shuaijuan; Chen, Baojiang (Frontiers in Veterinary Science, 2025)
Zearalenone (ZEA), a prevalent mycotoxin in animal feeds, is known to disrupt normal ovarian development and function due to its estrogenic activity. This study investigates the toxic effects of ZEA on the ovaries of meat rabbits and explores the underlying mechanisms. Ninety healthy 41-day-old Hyla male rabbits were randomly assigned into three groups. The control group received a basal diet, while the experimental groups were fed basal diets supplemented with 300 and 600 μg/kg ZEA, respectively. Each group consisted of 30 replicates, with one rabbit per replicate, and the experimental period lasted 42 days. The results showed that, compared to the control group, the ovarian index was significantly increased in the 600 μg/kg ZEA supplementation group (p < 0.05). In addition, ovarian tissue exhibited pathological changes, including follicular dilatation, thinning of the follicular granulosa, punctate necrosis of granulosa cells, deep stained cytosolic nuclei, and nuclear fragmentation. Compared to the control group, the 600 μg/kg ZEA supplementation group exhibited significantly elevated blood levels of gonadotropin-releasing hormone, luteinizing hormone, estradiol, malondialdehyde (MDA), and interleukin 1β (IL-1β) (p < 0.05). Conversely, total antioxidant power (TAOC) and glutathione peroxidase (GSH-Px) activities were significantly reduced in this group (p < 0.05). The level of MDA in the ovarian tissue of rabbits in the 600 μg/kg ZEA supplementation group was significantly elevated compared to the control group, while the activities of GSH-Px and TAOC were significantly reduced (p < 0.05). Moreover, the expression levels of luteinizing hormone receptor mRNA, heat shock protein 70 mRNA, tumor necrosis factor-α mRNA, and IL-1β mRNA in the ovarian tissue significantly increased, whereas the expression of copper and zinc superoxide dismutase mRNA was significantly decreased compared to the control group (p < 0.05). In conclusion, supplementation with 600 μg/kg ZEA induces oxidative stress and inflammatory responses in the ovaries of meat rabbits by modulating the expression of related genes. These effects disrupt ovarian development, cause pathological changes, and impair the secretion of reproductive hormones. This study is the first to report the toxic effects of ZEA on the ovaries of Hyla rabbits and provides preliminary insights into its underlying mechanisms.